Reconstructing the body classicism, modernism, and the First World War - Carden-Coyne, Ana (Oxford University Press, 2009)
From the ashes of war rose beauty, eroticism, and the promise of utopia. Ana Carden-Coyne investigates the cultures of resilience and the institutions of reconstruction in Britain, Australia, and the United States.